Penerapan Smart Tourism Dalam Pengelolaan Pariwisata Daerah Bojonegoro Berbasis GIS (Geographic Information System) - Pamungkas Ibnusiqin, Dhuta; Arianto, Yuri; Ayu Lestari, Vivin (Jurnal Teknik Ilmu dan Aplikasi, 2023)
The increasingly rapid development of technology, especially in information systems and telecommunications, makes access to information delivery very fast, coupled with reliable internet access. Developments have also occurred in GIS web applications. Web GIS can be used to publish village boundary maps to the community online, freely, and at any time. By using Leaflet as a web-based map, anyone can modify and access it at any time. Leaflet is one of the developments of GIS. The concept of developing technology studies and the tourism sector. Smart Tourism can describe the current situation regarding how development in the tourism sector has also been affected by the evolution of the rapid development of technology and information. This is what creates and bridges and unites micro businesses from local communities and nomads in the regions to the global market. Therefore, in this research, we will develop tourist attraction mapping based on Geolocation and Geographic Information System (GIS) using Leaflet technology to make it easier for tourists to find tourist attractions so that tourists not only know the tourist attractions, routes, current locations, and are able to find out about the facilities in the area. the tourist attraction area. This system was designed and implemented using Laravel, PHP, MySQL, Java Script, Bootstrap, and Leaflet. This system has also been tested by tourists and the results are that every tourist can enjoy the features of describing tourist attractions, destination routes, and making visit schedules.